The Association Between Antidepressant Treatment and Heart Rate Deceleration Capacity in Patients With Mood disorders—A Potential New Predictor of Sudden Cardiac Death - Okayasu H; Sugawara N; Fujii K; Ozeki Y; Yasui-Furukori N (Neuropsychiatric Disease and Treatment)
Hiroaki Okayasu,1 Norio Sugawara,1 Kumiko Fujii,2 Yuji Ozeki,2 Norio Yasui-Furukori1 1Department of Psychiatry, Dokkyo Medical University, Shimotsuga, Tochigi, Japan; 2Department of Psychiatry, Shiga University of Medical Science, Otsu, JapanCorrespondence: Hiroaki Okayasu, Department of Psychiatry, Dokkyo Medical University, School of Medicine, 880 Kitakobayashi, Mibu, Shimotsuga, Tochigi, 321-0293, Japan, Tel +81-282-86-1111, Fax +81-282-86-5187, Email hokayasu@dokkyomed.ac.jpPurpose: Patients with mood disorders treated with antidepressants are at high risk of sudden cardiac death, and QT interval prolongation has been as an indicator of sudden cardiac death, however there is no clarity. Recently, a decreased heart rate deceleration capacity (DC) has been regarded as an accurate predictor of cardiac mortality. We attempted to reevaluate the risk of sudden cardiac death associated with antidepressant use assessed via DC.Patients and Methods: We investigated the correlation of the DC of 107 patients with major depressive disorder (MDD) and bipolar disorder (BD), diagnosed by the Diagnostic and Statistical Manual of Mental Disorders, 5th edition, with prescribed doses of antidepressants or other psychotropic drugs via linear regression analysis. We then compared the DC of 68 age- and sex-matched healthy controls with that of 68 MDD patients.Results: DC was negatively correlated with both tricyclic antidepressant (TCAs) (PRC = − 3.62, 95% CI= − 5.69–-1,55, p< 0.001) and non-tricyclic antidepressant (non-TCAs) use (PRC = − 0.69, 95% CI= − 1.34–-0.042, p< 0.05) in a dose-dependent manner. Additionally, we found that MDD patients taking antidepressants had significantly lower DC compared to healthy controls (5.32 vs 7.60ms, p< 0.001).Conclusion: The use of TCAs would influence the decline in DC, and even the use of non-TCAs may influence the decline in DC when multiple medications are used. Evaluating DC may improve the predictive accuracy of sudden cardiac death in patients with mood disorders taking antidepressants.Keywords: deceleration capacity, antidepressant, sudden cardiac death, heart rate variability, QT interval, mood disorder, major depressive disorder